The innovation of a packaging for Songkok with QR code and augmented reality technology - Mohd Rahmat, Ahmad Haziq; Omar, Mastura; Rosnan, Shalida; Abdul Rani, Mohd Khairul Azahari; Daud, Bakri; Mohd Muslim Tan, Ellyana; Muhamad, Mohd Jamil; Mustafa Bakri, Ezrin (Academica Press Solutions, 2023)
The innovation of Songkok packaging with QR code and augmented reality is a revolutionary development in the traditional packaging of Songkok. The packaging using 300gsm material with one side coated paper and only need one die cut block. This packaging also highlights the use of QR codes and augmented reality technology to enhance the customer experience by providing a digital platform for product information, and interaction. By using QR codes, customers can access product information, contact, website, social media, and other interesting details by simply scanning the code with their smartphones. The augmented reality technology offers a 3D view of the Songkok, enabling customers to interact with the product virtually, examine it closely, and visualize how it would look when worn. This innovative packaging not only offers a new way of marketing the product but also elevates the customer experience, making it more interactive and engaging. Songkok packaging can take the form of boxes, or bags, depending on the material used and the intended function of the packing. The packaging is intended to preserve the Songkok from damage during movement and storage, as well as to make it easier to transport. Packaging may also be used as a marketing technique to increase the product's visual value and differentiate it from rivals. The packaging may be intended to represent the brand's identity, using colors, logos, and other branding elements to stand out on the marketplace.